Empowering ESP Teacher with Technology: Pedagogical Innovations in Vocational High Schools - Mustaqimah, Mustaqimah; Rafiqa, Rafiqa; Andi Adisaturrahimi, Andi Adisaturrahimi (Journal of ELT, Linguistics, and Literature, 2025)
The strategic integration of digital technologies into English for Specific Purposes (ESP) instruction has emerged as a critical dimension of pedagogical competence, particularly in vocational education settings where contextualized language learning is essential. This study investigates the digital pedagogical practices of an ESP teacher at a state vocational high school in Indonesia, framed by the National Teacher Competency Standards (Permendiknas No. 16/2007), specifically Standard 5, which emphasizes the effective utilization of information and communication technology (ICT) in teaching. Employing a qualitative case study design, data were gathered through systematic classroom observations, semi-structured interviews, and document analysis. The findings indicate that the teacher demonstrated consistent and deliberate integration of digital technologies across all phases of instruction—including lesson planning, delivery, and assessment—using a range of tools such as mobile learning applications, interactive multimedia, and online evaluation platforms. The teacher’s approach was marked by a strong alignment between digital strategies and students' vocational profiles, resulting in increased learner engagement and contextual relevance. This study contributes to the growing discourse on digital pedagogy in ESP by providing empirical insights into how individual teacher can leverage technology not merely as an instructional aid, but as a transformative tool to support vocationally aligned, learner-centered education. It concludes by emphasizing the importance of targeted professional development in digital pedagogy that bridges technical skill and pedagogical depth, particularly for ESP practitioners in vocational education contexts